Can Grafting Manage Fusarium Wilt Disease of Cucumber and Increase Productivity under Heat Stress? - Tarek A. Shalaby; Naglaa A. Taha; Mohamed T. Rakha; Hossam S. El-Beltagi; Wael F. Shehata; Khaled M. A. Ramadan; Hassan El-Ramady; Yousry A. Bayoumi (Plants, 2022)
Cucumber production is considered a crucial problem under biotic and abiotic stress, particularly in arid and semi-arid zones. The current study investigated the impact of grafted cucumber plants on five cucurbit rootstocks under infection with Fusarium oxysporum f. sp. cucumerinum alone and in combination with heat stress in two different locations (i.e., Kafr El-Sheikh and Sidi Salem) during the year of 2021. The rootstock of VSS-61 F1 displayed the highest level of resistance with values 20.8 and 16.6% for wilt incidence and 79.2 and 83.4% for the wilt reduction, respectively for both locations. This rootstock showed the lowest disease severity of fusarium wilt (15.3 and 12%), and high grafting efficiency (85 and 88%), respectively in both locations. Grafting also improved plant vigor and cucumber production under heat stress (40–43 °C). The rootstocks VSS-61 F1, Ferro and Super Shintoza significantly increased the total yield of cucumber plants compared to non-grafted cucumber and the rootstock Bottle gourd in both locations. Further studies are needed on grafted plants under multiple stresses in terms of plant biological levels, including physiological, biochemical and genetic attributes.